Pengaruh Pemberian Ekstrak Etanol Bawang Tiwai terhadap Hispatologi Ginjal Mencit (Journal of Tropical Pharmacy and Chemistry, 2012)
The ethanolic extract from the bulb of Eleutherine americana was investigated for subacute toxicity in Balb/C male mice. The parameter used on this research is kidney histophatological. During subacute toxicity study, bulb plant (0.52, 0,26 and 5.2 mg/kg b.wt) p.o. once daily for 30 days. The animals were sacrificed on the 30th day and the kidney were processed for histophatological. The result of descriptive observation histophatological in kidney shows there is inflammation in glomerulus with 2.6 mg/kg b.wt and 5.2 mg/kg b.wt dosage. There is oedem in tubulus for dosage given in In tubulus 0.52, 0,26 and 5.2 mg/kg b.wt